2017
DOI: 10.1007/s10339-017-0805-x
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, engagement, entrainment: the interaction dynamics of aesthetic experience

Abstract: A recent version of the view that aesthetic experience is based in empathy as inner imitation explains aesthetic experience as the automatic simulation of actions, emotions, and bodily sensations depicted in an artwork by motor neurons in the brain. Criticizing the simulation theory for committing to an erroneous concept of empathy and failing to distinguish regular from aesthetic experiences of art, I advance an alternative, dynamic approach and claim that aesthetic experience is enacted and skillful, based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 63 publications
(63 reference statements)
1
57
0
1
Order By: Relevance
“…Emotion is necessarily multi-dimensional, multi-scalar, and multimodal, taking on a variety of functional roles (Ratcliffe 2009;Stern 2004). In agreement with phenomenology that sees affect as connecting body, self, and world Fuchs 2013, we conceive of emotions relationally, in the case of making as arising from the interplay between agent and material (Brinck 2018b) and infusing the experiences of self and other with valence.…”
Section: Emotional Engagementsupporting
confidence: 57%
“…Emotion is necessarily multi-dimensional, multi-scalar, and multimodal, taking on a variety of functional roles (Ratcliffe 2009;Stern 2004). In agreement with phenomenology that sees affect as connecting body, self, and world Fuchs 2013, we conceive of emotions relationally, in the case of making as arising from the interplay between agent and material (Brinck 2018b) and infusing the experiences of self and other with valence.…”
Section: Emotional Engagementsupporting
confidence: 57%
“…Remarkably, there is a lack of research on how interactivity affects the aesthetic experience. Previous research alludes to certain elements of interactivity, such as movement, being a crucial part of the aesthetic experience (Brinck, 2018). Brinck (2018, p. 209) argues in her paper that "the more invitations to interact from artworks that a viewer responds to and the more ways of responding she masters, the more she will learn about her real possibilities to explore art visually and her ability to control the process".…”
Section: Interactive Artmentioning
confidence: 99%
“…Ever since the humanity existed, it was realized that experiencing beauty has a positive impact on the psychology of human beings and their performance at all levels. Cognitive studies found that esthetic experience emerges from bodily and emotional engagement with works of art via complementary processes that modulate the overall affect and attitude [13]. Moreover, studies in the field of neuroaesthetics used functional MRI to demonstrate that experiencing beauty induces specific patterns of cerebral activity, like the activation of field A1 of the medial orbitofrontal cortex by beautiful visual or auditory stimuli [14] and the activation of caudate nucleus during experience of visual beauty [14,15] in a fashion similar to that which occurs during romantic love [16,17].…”
Section: The Esthetic Aspect Of Neuroendoscopy and Its Valuementioning
confidence: 99%